It isn’t just Mom: Gendered provision of family and home responsibilities among emerging adults during COVID-19 - Navarro, Jessica L.; Brown, Morgan; Jensen, Todd; Weinstein, Mariani; Jensen, Michaeline (Frontiers in Psychiatry, 2024)
Media and research reports have highlighted the disproportionate burden of home and family responsibilities shouldered by women and mothers due to COVID-19-related school/childcare shutdowns. This cross-sectional study extends this line of inquiry to emerging adults. Our study of 329 diverse emerging adults suggests that young women took on more home/family responsibilities than young men amidst the pandemic, and that these duties were associated with symptoms of depression. However, results also indicate that emerging adults who reported greater home/family responsibilities amidst the pandemic also experienced more quality family time, suggesting that pandemic-related challenges may have also been accompanied by opportunities for family connection. Contrary to previous research that has shown home/family responsibilities to be concentrated by SES and race/ethnicity, we found that participants uniformly endorsed COVID-19-related impacts on home/family responsibilities across these demographic distinctions. This could reflect the ubiquity of COVID-19’s impact; across race/ethnicity and class—but differentially by gender—young adults faced significant challenges in taking on new home/family roles.